Practical synthesis of 3-aryl anthranils via an electrophilic aromatic substitution strategy. Issue 7 (3rd February 2022) - Gao, Yang; Yang, Simin; She, Minwei; Nie, Jianhong; Huo, Yanping; Chen, Qian; Li, Xianwei; Hu, Xiao-Qiang
Abstract : A practical route for the synthesis of valuable 3-aryl anthranils from readily available anthranils and simple arenes has been achieved through an electrophilic substitution and rearomatization sequence by employing Tf2 O as an effective activator. Abstract : We report a practical route for the synthesis of valuable 3-aryl anthranils from readily available anthranils and simple arenes by using the classical electrophilic aromatic substitution (EAS) strategy. This transformation goes through an electrophilic substitution and rearomatisation sequence by employing Tf2 O as an effective activator. A wide range of arenes were compatible in this transformation, delivering various structurally diversified 3-aryl anthranils in good yields and high regioselectivity. In addition, a variety of readily available feedstocks such as olefins, alkenyl triflates, silyl enolethers, carbonyl compounds, thiophenols and thiols could also participate in the reaction to achieve the C3 alkenylation, alkylation and thioetherification of anthranils. Of note, the synthesized 3-aryl anthranils proved to be a highly robust platform to access a series of biologically active compounds, drug derivatives and organic optoelectronic materials.